Tools for gauging the capacity of salmon spawning substrates. Issue 1 (4th November 2015) - Overstreet, Brandon T.; Riebe, Clifford S.; Wooster, John K.; Sklar, Leonard S.; Bellugi, Dino
ABSTRACT: We present a set of river management tools based on a recently developed method for estimating the amount of salmon spawning habitat in coarse‐bedded rivers. The method, which was developed from a mechanistic model of redd building by female salmon, combines empirical relationships between fish length, redd area, and the sizes of particles moved by fish during spawning. Model inputs are the grain‐size indices D 50 and D 84 and an estimate of female fish length, which is used to predict the size of the redd that they will build and the size of the largest particle that they can move on the bed. Outputs include predictions of the fraction of the bed that the fish can use for redd building and the number of redds that they can build within the useable area. We cast the model into easy‐to‐use look‐up tables, charts, an Excel worksheet, a JavaScript web applet, and a MATLAB user interface. We explain how these tools can be used in a new, mechanistic approach to assessing spawning substrates and optimizing gravel augmentation projects in coarse‐bedded rivers. © 2016 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd.